Obstacles to Implementing Total Quality Management in Technical Education Institutions (A Review Analytical Study) (Comprehensive Journal of Science, 2025)
This study aims to explore the factors that hinder the implementation of total quality management in technical education institutions in Libya, relying on a descriptive-analytical approach and conducting a comprehensive review of quality-related academic programs and activities (seminars, conferences, forums, and workshops) since 2024. The results concluded that the main challenges lie in weak training programs, difficulties related to teaching methods, in addition to limited financial resources that restrict the sustainability of quality